Konsep Asas dan Pembahagian Ilmu Menurut Manuskrip Melayu: Suatu Penelitian Terhadap MSS 2906 (B) Tibyan al-Maram: The Basic Concept and Classification of Knowledge According to Malay Manuscript: A Study on MSS 2906 (B) Tibyan al-Maram - Mamat, Mohd Anuar; Jusoh, Che' Razi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The article discusses on issues regarding the basic concept of knowledge and its classification according to Malay manuscript, which is MSS 2906 (B) Tibyān al-Marām Ṭalibah al-Ṭalabah. According to codicological analysis, the manuscript is originated from Aceh and it was written at the end of 18th century or early 19th century. The manuscript is in the collection of National Center of Malay Manuscript, National Library of Malaysia. It was translated from Arabic entitled Ṭalibah al-Ṭalabah fī Ṭarīq al-‘Ilm li man Ṭalabah written by Sadīd al-Dīn Muḥammad al-Kāshgharī (d.705H/1305M) into Malay language with Jawi alphabet. Based on content analysis method, there are two important aspects which are the focus of this article. Firstly, the basic concept of knowledge while the second aspect is regarding the classification of knowledge a well as its preference in education. The discussion on these two aspects is important in order to understand the concept of knowledge according to the Malay manuscript in Islamic education, especially based on Tibyān al-Marām, which is the only extensive manuscript on knowledge and education. By understanding the concept and the classification of knowledge, it will give a proper direction for the transformation of education and the efforts on integration of knowledge particularly at the higher level of education.